The gut-brain paradox : improve your mood, clear brain fog, and reverse disease by healing your microbiome - Gundry, Steven R.; Lipper, Jodi (Paradox series, 2025)
"In his previous ... books, Steven R. Gundry taught readers how to reverse disease and improve health and well-being by preventing and repairing leaky gut. In The Gut-Brain Paradox, he delves even moredeeply into the mysterious and long misunderstood world of the human microbiome. Here Dr. Gundry uncovers the complex and multifaceted ways in which our microbes are controlling the health and functioning of our brains, and how the gut-brain connection is made long before we are even born. [This book] shines a ... light on how the one-two punch of leaky gut and gut dysbiosis, together driven by western diets, overuse of antibiotics and other medications, and environmental toxins, allow pathogenic bacteria to take over"--